An Exploratory Study of Hygiene, Sanitation and Health Awareness of People at Some Prominent Public Places in Delhi - Raychaudhuri, P. S.; Singh, Aditi (Prabandhan: Indian Journal of Management, 2011)
This article is an attempt to highlight serious problems of urbanization that the National Capital Territory of Delhi is facing today. It also brings to light several unknown or not properly understood aspects of the subject. The sky high buildings, flyovers and roads flooded with the cars, skyrocketing malls and multiplexes - that are the vibrant gateway to shop for branded products; this is the way Delhi looks, but is this the true picture of Delhi? Does it encompass all that one identifies with Delhi's urban scene? We have tried to understand all these aspects and efforts have been made to analyze the cases of lack of awareness among the public at large about the hygiene and sanitation and, responses of the public about private participation for improving the condition of hygiene and sanitation at various public places in Delhi.